Adjusting plasma or serum zinc concentrations for inflammation: Biomarkers Reflecting Inflammation and Nutritional Determinants of Anemia (BRINDA) project. Issue 4 (8th April 2020) - McDonald, Christine M; Suchdev, Parminder S; Krebs, Nancy F; Hess, Sonja Y; Wessells, K Ryan; Ismaily, Sanober; Rahman, Sabuktagin; Wieringa, Frank T; Williams, Anne M; Brown, Kenneth H; King, Janet C
ABSTRACT: Background: The accurate estimation of zinc deficiency at the population level is important, as it guides the design, targeting, and evaluation of nutrition interventions. Plasma or serum zinc concentration (PZC) is recommended to estimate zinc nutritional status; however, concentrations may decrease in the presence of inflammation. Objectives: We aimed to assess the relation between PZC and inflammation in preschool children (PSC; 6–59 mo) and nonpregnant women of reproductive age (WRA; 15–49 y), and to compare different inflammation adjustment approaches, if adjustment is warranted. Methods: Cross-sectional data from 13 nationally representative surveys (18, 859 PSC, 22, 695 WRA) from the Biomarkers Reflecting Inflammation and Nutritional Determinants of Anemia (BRINDA) project were analyzed. Correlation and decile analyses were conducted, and the following 3 adjustment methods were compared if a consistent negative association between PZC and C-reactive protein (CRP) or α-1-acid glycoprotein (AGP) was observed: 1 ) exclude individuals with CRP > 5 mg/L or AGP > 1 g/L; 2 ) apply arithmetic correction factors; and 3 ) use the BRINDA regression correction (RC) approach. Results: In 6 of 12 PSC surveys, the estimated prevalence of zinc deficiency increased with increasing CRP deciles, and to a lesser extent, with increasing AGP deciles. In WRA, the association of PZC with CRP and AGP was weak and inconsistent. In the 6 PSC surveys in which adjustment methods were compared, application of RC reduced the estimated prevalence of zinc deficiency by a median of 11 (range: 4–18) percentage points, compared with the unadjusted prevalence. Conclusions: Relations between PZC and inflammatory markers were inconsistent, suggesting that correlation and decile analyses should be conducted before applying any inflammation adjustments. In populations of PSC that exhibit a significant negative association between PZC and CRP or AGP, application of the RC approach is supported. At this time, there is insufficient evidence to warrant inflammation adjustment in WRA.